The Bhagavad Gita - Easwaran, Eknath (Ahmedabad Jaico publishing house, 2022)
The Bhagavad Gita opens, dramatically, on a battlefield, as the warrior Arjuna turns in anguish to his spiritual guide, Sri Krishna, for answers to the fundamental questions of life. Easwaran's introduction places the Gita in its historical setting and brings out the universality and timelessness of its teachings.
Keywords: Hinduism